Natural history and prognostic factors for localised small bowel adenocarcinoma. Issue 6 (13th November 2020) - Colina, Andreina; Hwang, Hyunsoo; Wang, Huamin; Katz, Matthew H G; Sun, Ryan; Lee, Jeffrey E; Thomas, Jane; Tzeng, Ching-Wei; Wolff, Robert A; Raghav, Kanwal; Overman, Michael J
Abstract : Objective: Small bowel adenocarcinoma (SBA) is a rare malignancy with limited evidence regarding outcomes after curative resection of localised disease. We aimed to evaluate presentation and prognostic factors affecting overall survival (OS), relapse-free survival (RFS) and recurrence of SBA. Methods: Consecutive patients with completely resected localised SBA (1979–2019) were retrospectively reviewed for presentation, patient and tumour characteristics, perioperative treatment, recurrence, outcomes, and prognostic factors. Results: Among 257 total patients, median age was 58 years. Primary location was in the duodenum, jejunum and ileum in 52%, 29%, and 19% of patients, respectively. Median OS was 57.5 months and median follow-up was 40 months. In multivariate analysis, lymph node involvement, lymphovascular invasion, histologic grade and race were independent predictors of RFS, while race, stage and histologic grade were independent predictors of OS. No significant difference in OS or RFS was seen when evaluating the role of perioperative treatment. Median time to diagnosis from first medical evaluation was 31 days and did not change over time. Overall recurrence rate was 56%. Recurrence rate was higher in ileal (77%), than duodenal (54%) and jejunal (65%) SBA (p=0.01). Recurrence presented most commonly as distant metastasis (71%). Proficient mismatch repair was associated with decreased risk of locoregional recurrence (LR) but increased risk of distant recurrence (DR) when compared with deficient mismatch repair (dMMR) in univariate analysis. Conclusions: Despite advances in diagnostic modalities, this study did not show any improvement in earlier diagnosis of SBA over the course of the past three decades. The predominant pattern of disease recurrence was distant across all SBA locations, but dMMR status demonstrated a robust predilection for LR as opposed to DR. Perioperative treatment did not improve outcomes; however, a lower stage disease was seen in patients that received neoadjuvant therapy, suggesting further exploration of this approach.